Gibberellin biosynthesis and signalling during development of the strawberry receptacle - Csukasi, Fabiana; Osorio-Algar, Sonia; Gutiérrez, José R.; Kitamura, Jun; Giavalisco, Patrick; Nakajima, Masatoshi; Fernie, Alisdair R.; Rathjen, John R.; Botella-Mesa, Miguel Ángel; Valpuesta-Fernández, Victoriano; Medina-Escobar, Nieves (Wiley, 2011)
Essential factors controlling the growth and development of strawberry (Fragaria × ananassa) fruit are poorly characterized at the molecular level. The roles played by different hormones in these processes remain largely unknown (Seeram, 2008). The strawberry achenes (a combination of seed and ovary tissue sited at the base of each pistil) are the true fruits of this species and are embedded in the epidermal layer of the receptacle connected by vascular bundles (Perkins-Veazie, 1995). More than 60 yr ago it was proposed, based on physiological studies, that fertilized achenes govern the fate of the receptacle and, at least during the early stages of fruit development, auxin synthesized in the achenes promotes the growth of the receptacle (Nitsch, 1950; Given et al., 1988). Thus, the removal of achenes from unripe fruits causes the inhibition of growth and expansion, and the induction of a set of ripening-related genes (Manning, 1994; Medina-Escobar et al., 1997; Harpster et al., 1998; Aharoni et al., 2002)
Keywords: Fresas; gibberellins; strwaberry; fruit